Designing A Website for Teaching Arabic Grammar Rules in Al-Ajrumiyyah Book for Self-Directed Learners - Yusuf Aziz Mustofa; Abdul Hafidz bin Zaid; Agus Yasin (UIN Sunan Gunung Djati Bandung, 2025)
Arabic grammar (nahwu) in higher education is often taught through memorization and static texts, which hinders systematic understanding and independent practice. This study developed and evaluated Jurumiyah.ID, a web-based learning platform that organizes the Matn al-Ājurrūmiyyah and selected syarah, adds cross-referenced rules, and embeds interactive quizzes to support self-directed learning. The development followed a Research & Development approach using the ADDIE Model, and Waterfall SDLC adaptation. Core features include searchable matn and rule summaries, cross-references among interdependent rules, and short formative tests designed for rapid feedback and review. Methodologically, the study employed a one-group pretest–posttest design to estimate learning gains attributable to structured practice on Jurumiyah.ID. The objective test bank was constructed from 30 items and reduced to 10 valid items through corrected item total correlations; internal consistency was acceptable (Cronbach’s α = 0.794). Participants (n = 40) were students from Qur’anic Studies and Islamic Education programs at Universitas Islam Darussalam Ciamis. Post-test performance exceeded pre-test performance, indicating measurable improvement in students’ understanding of key Ajurrūmiyyah rules after using web. Psychometric screening supports the adequacy of the instrument for detecting change (10 valid items; α = 0.794), and the design isolates short-term learning gains under guided self-study conditions. The platform’s modular design and searchable knowledge base enable scalable integration into course syllabi and independent study. Future work should extend to controlled comparisons and broader content coverage to strengthen causal inference and generalizability.